Determinant Factors of Noncompliant Behavior in Treatment with Tuberculosis (TB) Patients - Asriwati Amirah; Juliandi Harahap; Khairatunnisa Khairatunnisa; Dian Mayasari Siregar; Senang Hati Bazikho (PT.Mantaya Idea Batara, 2026)
Background: Pulmonary tuberculosis (TB) is a directly transmitted disease and poses a major threat to human resource development, thus requiring more serious attention from all parties. The objective of this study is to analyze the determinants of treatment non-compliance among pulmonary tuberculosis patients in South Nias Regency. Methods: This study uses a quantitative research design with a cross-sectional approach. The sample in this study used stratified sampling of 6 community health centers with the highest number of TB cases. The sample size was 72 respondents with pulmonary tuberculosis in the working area of the South Nias Regency Health Office. Results: Based on the analysis results, knowledge (p=0.003), duration of treatment (p=0.004), medication supervision (p=0.000) are related to the support of traditional leaders (p=0.001) towards tuberculosis treatment adherence in South Nias district. Conclusions: The recommendations in this study are for health workers to collaborate with various sectors, especially traditional leaders, families, and community organizations, to help provide education and reduce stigma in order to support TB treatment adherence and strengthen medication supervision (PMO) to prevent drug resistance, which can lead to prolonged treatment and the risk of TB transmission.